Quintessential Ambedkar’s Contribution to Women Empowerment - Shamala M. Ratnakar, (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2026)
Dr. B. R. Ambedkar was a great leader and an epoch maker of modern India. He was born in a poor family from the Mahar community, where people faced untouchability and discrimination. From his childhood, he saw pain, humiliation, and unfair treatment. This made him strong and determined to fight for justice. Dr. B.R. Ambedkar believed in dignity, equal opportunities, and respect for everyone. He worked hard to empower women and the poor people of society. He said that the progress of a society is measured by the progress of women. He understood that books like Manusmriti had unfair rules that kept women weak and dependent, which led to gender discrimination. So, he protested against such ideas. He also tried to bring new laws like the Hindu Code Bill to give women equal rights in family, property, and marriage. Even though people opposed him, he never gave up. He believed women and men are equal and should live with mutual respect and dignity.
Keywords: Dr. B.R. Ambedkar; Women Empowerment; Caste and Gender Discrimination; Equality